The Native Speaker Programme – the coin has two sides - Fatiha Senom,; Juliana Othman,; Saedah Siraj, (Penerbit Universiti Kebangsaan Malaysia, 2016)
The aim of the study is to gain an insight into novice ESL teachers’ diverse experiences as mentees in a mentoring programme, the Native Speaker Programme. Employing a multiple case study, the study was conducted among four novice primary school ESL teachers in Malaysia through in-depth interviews and observations. The findings indicated that there are two sides of the coin of being the mentees in the Native Speaker Programme, positive as well as less positive experiences. While some of the novice teachers had the opportunity to work with mentors with positive personal qualities who played constructive roles in facilitating their professional development through effective mentoring strategies, some experienced the opposite. The two contradictory experiences represent two sides of the same coin.